Fabrication of a cost-effective lemongrass (Cymbopogon citratus) membrane with antibacterial activity for dye removal. Issue 58 (23rd October 2019) - Cai, Zengxiao; Remadevi, Rechana; Al Faruque, Md Abdullah; Setty, Mohan; Fan, Linpeng; Haque, Abu Naser Md Ahsanul; Naebe, Maryam
Abstract : Dye wastewater has caused severe environmental and health problems. In this work, we have fabricated a novel low-cost membrane with good methylene blue dye adsorption and antibacterial property from naturally sustainable lemongrass ( Cymbopogon citratus ). Abstract : Dye wastewater has attracted much attention due to its severe environmental and health problems. The main challenge of separating dyes from wastewater, using adsorption, is developing a functional adsorbent that is cost-effective and sustainable. In this work, we have fabricated a novel low-cost membrane with antibacterial properties from naturally sustainable lemongrass (LG). Lemongrass was cut and milled into powder, then dissolved to prepare a lemongrass membrane. Graphene oxide (GO) was also included to prepare a LG/GO composite membrane. The physiochemical and antibacterial properties of membranes were evaluated and their dye adsorption capability was examined using methylene blue (MB) dye at different concentrations. The kinetic study revealed that the MB adsorption process complied with the pseudo second-order model. The lemongrass membrane showed a rough surface morphology, high reduced modulus and hardness, yet comparable dye adsorption to the LG/GO composite membrane. Considering the natural sustainability of lemongrass as an abundant cellulosic resource, its excellent dye adsorption, antibacterial properties and low cost as well as the facile fabrication technology, the lemongrass membrane could be a promising candidate for dye removal from wastewater with easy separation after use.